Answer:
- f(x) = 2x -2/3
- f(3) = 5 1/3
Step-by-step explanation:
We solve an equation for a specific variable by using inverse operations to undo what is done to the variable. The resulting function is evaluated by substituting the given value for the variable.
__
<h3>a.</h3>
We are given the equation ...
6x -3y = 2
Solving for y, we get ...
6x -2 = 3y . . . . . add 3y-2 to both sides
2x -2/3 = y . . . . . divide by 3
f(x) = 2x -2/3 . . . . write using functional notation
__
<h3>b.</h3>
To find f(3), we use x=3 in the function.
f(3) = 2(3) -2/3 = 6 -2/3
f(3) = 5 1/3
Answer:
In order to get this perfect square trinomial, the factored form will be (a - b)^2
Step-by-step explanation:
We know this because it follows the rule of perfect squares in which the ends are both squares and the middle term is -2 times each term.
Answer:
Where is the table
Step-by-step explanation:
I cant answer without it